Numerical simulations of the fatigue damage evolution at a fastener hole treated by cold expansion or with interference fit pin. (March 2016) - Sun, Ying; Hu, Weiping; Shen, Fei; Meng, Qingchun; Xu, Yuanming
Abstract: Numerical simulations of the fatigue damage evolution at a hole in a plate treated by cold expansion or with interference fit pin is performed based on continuum damage mechanics and the finite element method. The damage-coupled Chaboche plasticity constitutive model is used to model the mechanical behavior of material. Plastic-strain-based and stress-based equations are used to calculate damage accumulation. The process of the hole cold expansion or pin interference fit and the subsequent fatigue damage evolution are simulated. The predicted results agree well with the experimental data available in the literature. Result shows that the beneficial effect of cold expansion and interference fit on the fatigue life improvement of a fastener hole is not only due to the reduction in maximum stress or stress amplitude, but also to the change in the fatigue damage evolution at the critical location. Highlights: The CDM approach provides an insight into the fatigue damage evolution and associated material degradation of cold expanded and pin interference fit fastener holes. The predicted results are in good agreement with the experimental results available in the literature.